Semantic Aspect of Indonesian Advertisements for Overseas Promotion : Case Study on Wonderful Indonesia Youtube Channel - Aviza, Aviza Alyama; Harmoko, Danang Dwi; Suwarsito, Suwarsito (English Journal Antartika, 2023)
This study aims to identify the types of meaning and aspects of meaning contained in the advertisement Wonderful Indonesia YouTube channel this research uses a descriptive qualitative method. Data in advertisements, The Largest Matrilineal Society in the World, Borobudur Temple-Where History Lives Forever and We Love Bali are analyzed using semantic theory. The results of this study indicate that there are 12 types of meaning; 50 Grammatical, 156Lexical, 30 referential, 39 non-referential, 33 Denotative, 21 Term meaning, 1 Associative meaning. There are 3 aspects of meaning; 3 senses, 7 tones, 3 intentions, 1 feeling. The dominant types of meaning found in this advertisement are Grammatical meaning, Lexical meaning, and non-referential meaning. The most dominant aspect of meaning found in this advertisement is Tone. This research is important to know the message conveyed by the speaker in the advertisement. Keyword: Advertisements, Aspect of Meaning, Semantics, Types of Meaning